Challenges in the management and diagnosis of complications in a patient with cavernous sinus thrombosis - Khranovska, Margaryta; Sholomon, Svitlana (The Ukrainian Scientific Medical Youth Journal, 2025)
the prevalence and main etiological factors of cavernous sinus thrombosis are highlighted, a diagnostic algorithm for identifying the causes and possible complications of this pathology is presented. Clinical observation is described.